The Effectiveness of Speaking Instruction through Task-Based Language Teaching - Noor Malihah (Register Journal, 2010)
Speaking is a crucial part of second language learning and teaching. Teaching speaking is not merely to let students to repeat or memorize dialogues, but they should be able to use the utterance to communicate in the real situations. Teachers’ attitudes to respond the students thought and opinion is important, as they should not be forced to speak and putthem in the deep anxiety, but we invite the learners to use any languages in the performance of oral tasks where teachers give a task and learners complete the task. Teachers should be able to create such situations where students hold meaningful tasks that will promote their speaking proficiency. This can be realized when students works with their friends in groups to complete a task. Task-Based approach is the alternate to solve the problem where learning is developed through performing a series of activities as steps towards successful task realization.Key words: Language learning and teaching; speaking instruction; taskbasedapproach